Performance and Behavior Analysis of Single-Electrode Triboelectric Nanogenerator for Energy Harvesting Floor Tiles - Yingyong, Phonexai; Thainiramit, Panu; Vittayakorn, Naratip; Isarakorn, Don (My University, 2020)
A triboelectric nanogenerator (TENG) is a promising candidate for harvesting the wasted energy from the ambient environment and utilizing it as an independent power source for batteries used in wearable and portable devices as well as sensing systems. This paper investigated the performance and behavior of triboelectric energy harvesters based on energy harvesting floor tiles by applying different mechanical input parameters such as contact gap, velocity, and vibration frequency to characterize the electrical characteristics while maintaining the applied pressure of 600 kPa and temperature. The results revealed that massive air gap displacement tends to generate higher electrical output. This demonstrated that the device could generate 2294.14 μW of optimal power and 95.50 μJ of total energy in 10 s at the mechanical excited frequency of 2 Hz with a fixed gap displacement of 5 mm. Moreover, the output power is proportional to the velocity of the cover plate movement. In contrast, varying the relative humidity (%RH) showed that the TENG could generate high electrical output at low relative humidity. The proposed work demonstrates that the TENG can function as an energy-harvesting device from low-frequency mechanical vibration for energy harvesting floor tiles.
Keywords: energy-harvesting floor tile; low-frequency vibration energy harvesting; triboelectric energy harvesting; triboelectric nanogenerator